Creating synergies for business transformations : Brigade Enterprises Ltd. - Khanna, Varun; Kaul, Asha (London : SAGE Publications Ltd, 2017)
In 2009 Brigade Enterprises Limited (BEL), with operations in the real estate sector and construction in South India, prepared a blueprint for implementing Total Transformation in the organization. A central communication channel was identified as an area for improvement. Active and passive measures were adopted to make the internal communication vibrant, which would, it was envisioned, change organizational culture and bring about attitudinal change. However, the review after 18 months pointed towards gaps in the existing model. Should BEL continue with the existing strategies or amend? Given the organizational dynamics, what new changes, if necessary, can be initiated?
Originally published: Khanna, V., & Kaul, A. (2013). Creating synergies for business transformations : Brigade Enterprises Ltd. COMM0010. Ahmedabad: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Brigade Enterprises Limited (BEL); Real estate business -- India, South -- Case studies; Small business -- India, South -- Case studies; Organization change -- India, South -- Case studies